PENERAPAN KONSEP 7 HABITS OF HIGHLY EFFECTIVE KEPADA PELAKU UMKM KOTA TEGAL - Ashari, Ilham Akbar; Desi Maola Ayu Saputri; Ulul Absor; Sri Rahayu; Apriyani; Wynee Inayah Ekasari (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service activity aims to provide an understanding of the basic concepts of modern business development, including management, marketing, and operational management, as well as fostering an innovative, independent, and entrepreneurial mindset that is in line with the needs of the modern era. The program was implemented in Tegal City, targeting SMEs who need improvement related to business development. The methods used included initial observation, preparation of training materials, training implementation, and evaluation. The results of the activity showed an increase in participants' understanding of the importance of effective habits that SMEs can implement in developing their modern businesses. This creative approach was able to increase SMEs' motivation to implement effective habits so that business development is more disciplined, structured, and easy to communicate.